PENGUKURAN TINGKAT PEMAHAMAN DAN IMPLEMENTASI SAK EMKM PADA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) - Surachman, Surachman (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This research aims to measure the level of understanding and implementation of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in micro, small and medium enterprises (MSMEs), with a focus on case studies at the Rizky Collection. The research method used is qualitative with a descriptive approach. The research results highlight that the recording system at Rizky Collection is still simple, limited to recording product sales. Understanding of preparing financial reports in accordance with SAK EMKM also appears to be minimal among business managers. This limitation affects Rizky Collection's ability to prepare financial reports that reflect applicable standards. Research findings show that the preparation of financial reports based on SAK EMKM needs to be improved, considering that financial reports have an important role as indicators of the financial performance of a business entity. This condition shows the need for efforts to improve understanding and implementation of SAK EMKM among MSMEs, by paying special attention to the preparation of financial reports that are accurate and comply with standards